Translating cuneiform symbols using artificial neural network - Arwa Hamed Salih Hamdany; Raid Rafi Omar-Nima; Lubab H. Albak (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Cuneiform language is an old language that was invented by the people of Sumerian nation. It is an essential language for many archeologists. Especially who are interested in studying and investigating the old nations of Iraq. Dealing with this type of language usually requires specialist to translate its symbols, which are basically forms of nail shapes. This study presents a new approach to translate the cuneiform writing by employing artificial neural network (ANN) technique. Effectively, multi-layer perceptron (MLP) neural network has been adapted for translating the Sumerian cuneiform symbol images to their corresponding English letters. This work has been successfully established and it attained 100%.